2005
DOI: 10.1016/j.jhep.2004.12.034
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro model of hepatitis C virus genotype 3a-associated triglycerides accumulation

Abstract: Consistent with observations in chronic hepatitis C patients, the in vitro expression of HCV genotype 3a core protein is the ideal candidate model for studying the mechanisms of HCV-associated steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
117
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 25 publications
18
117
0
1
Order By: Relevance
“…This effect is relatively modest as compared with the effect of HCV core and the NS4B co-expression system (23-fold). In fact, there is a genotype difference in steatosis induction (46). Because we for an additional 12 h. Cells were harvested and then luciferase activities were determined.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is relatively modest as compared with the effect of HCV core and the NS4B co-expression system (23-fold). In fact, there is a genotype difference in steatosis induction (46). Because we for an additional 12 h. Cells were harvested and then luciferase activities were determined.…”
Section: Discussionmentioning
confidence: 99%
“…31885-023) supplemented with 10% fetal bovine serum, 100 U/ml penicillin, and 100 g/ml streptomycin (all from Invitrogen Life Technologies). We transfected pIRES2-EGFP plasmids containing the HCV 3a or 1b core-encoding region 17 …”
Section: Cell Culture Transfection and Flow Cytometrymentioning
confidence: 99%
“…8,14,15 Given its impact on liver disease progression 8 and response to antivirals, 16 unraveling the interaction between HCV and insulin signaling is of the utmost relevance. We used our model of transient expression of the core protein of different genotypes of HCV 17 to assess the interaction of HCV genotype 3a with the insulin signaling, using as comparison the genotype 1b, for which some data have already been reported. 12 We focused our attention on the IRS-1 and IRS-2 levels and on the mechanisms potentially implicated in their regulation.…”
mentioning
confidence: 99%
“…Viral steatosis is mostly reported in patients with genotype 3a, in whom fat accumulation correlates with HCV replication levels in serum and liver and disappears after successful antiviral therapy, strongly suggesting a direct role of specific viral products in the fat deposition. To address the role of specific HCV genotype on lipid accumulation in cells, Abid and coworkers [12] developed an in vitro model to study the effect of the core protein belonging to several viral genotypes (1b, 2a, 3a, 3h, 4h and 5a). They concluded that the pattern observed in Huh7 cells upon expression of the six core proteins largely corroborated the phenotype seen in vivo.…”
Section: Pathogenesis Of Steatosis In Hepatitis Cmentioning
confidence: 99%